(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2022)
Mitochondrial Replacement Techniques (MRTs), designed to prevent mitochondrial diseases, are far from being an efficient and safe opportunity to eradicate mitochondrial DNA’s disorders. Indeed, there are still many scientific, ethical, and social concerns. Particularly when it comes to identity issues for MRT-conceived people and non-therapeutical uses. This paper aims to suggest some reflections on these topics, without overlooking scientific grounds and regulatory references.